2024
DOI: 10.3389/fonc.2023.1299384
|View full text |Cite
|
Sign up to set email alerts
|

The potential applications of artificially modified exosomes derived from mesenchymal stem cells in tumor therapy

Yilin Song,
Quanlin Song,
Daosheng Hu
et al.

Abstract: Mesenchymal stem cells (MSCs) have tumor-homing ability and play critical roles in tumor treatment, but their dual influences on tumor progression limit their therapeutic applications. Exosomes derived from MSCs (MSC-exosomes) exhibit great potential in targeted tumor treatment due to their advantages of high stability, low immunogenicity, good biocompatibility, long circulation time and homing characteristics. Furthermore, the artificial modification of MSC-exosomes could amplify their advantages and their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 164 publications
0
1
0
Order By: Relevance
“…Such EVs have been shown to inhibit cancer cell growth, induce apoptosis and suppress epithelialmesenchymal transition in oral squamous cell carcinoma and cervical cancer [83,84]. Other approaches include vesicle loading with specific miRNAs, siRNAs, mRNAs, ncRNAs, proteins and peptides that have previously shown anti-tumour activity [69,85,86]. Some studies have reported the use of MSC-EVs to counteract chemoresistance in glioblastoma multiforme cells by delivering anti-miR-9, with promising results in reversing the chemoresistance of this tumour [87].…”
Section: Msc-derived Extracellular Vesiclesmentioning
confidence: 99%
“…Such EVs have been shown to inhibit cancer cell growth, induce apoptosis and suppress epithelialmesenchymal transition in oral squamous cell carcinoma and cervical cancer [83,84]. Other approaches include vesicle loading with specific miRNAs, siRNAs, mRNAs, ncRNAs, proteins and peptides that have previously shown anti-tumour activity [69,85,86]. Some studies have reported the use of MSC-EVs to counteract chemoresistance in glioblastoma multiforme cells by delivering anti-miR-9, with promising results in reversing the chemoresistance of this tumour [87].…”
Section: Msc-derived Extracellular Vesiclesmentioning
confidence: 99%